What is good and what is right: What relationship? - Turco, Giovanni (Derecho Público Iberoamericano, 2020)
The text focuses on the relationship between what is right and what is good, from a legal-political perspective. The latter represents an age-old question –posed both by the reality of lived experience as well as by doctrinal and philosophical thought– with respect to which the jurist is inescapably compelled to pronounce himself. It is a matter of understanding both the substance of the two terms and the essential priority of one with respect to the other. In the line of modernity (notably, starting from Thomas Hobbes) both concepts are made positive and immanent. What is good becomes the outcome of what is right, and this is understood as the effect of the legislator implementing his will. The issue has recently been reconsidered by both William Ross and Jürgen Habermas. In classical thought the problem emerges clearly in the Republic of Plato, and then finds particular development in the treatment [...].